2009
DOI: 10.1007/s00330-008-1266-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided removal of foreign bodies: personal experience

Abstract: Foreign bodies (FBs) retained in the soft tissues are a common reason for medical consultation, and usually consist of wooden or metal splinters or glass shards. Failure to remove foreign bodies is likely to give rise to acute or late complications, such as allergies, inflammation or infection, that may be severe. The surgical removal of an FB is invasive, costly and technically challenging. The procedure may fail in some cases and carries the risk of complications. Our study describes a technique for the ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 19 publications
(32 reference statements)
0
81
1
2
Order By: Relevance
“…10 USG has been used not only for detection and localization but also to guide removal of the foreign bodies. 11,12 Our result showed that tissue harmonic sonography was 100% sensitive for the detection of the wooden foreign bodies.…”
Section: Discussionmentioning
confidence: 69%
“…10 USG has been used not only for detection and localization but also to guide removal of the foreign bodies. 11,12 Our result showed that tissue harmonic sonography was 100% sensitive for the detection of the wooden foreign bodies.…”
Section: Discussionmentioning
confidence: 69%
“…Usually the foreign body is a splinter of wood or a sliver of metal or glass which needs prompt removal to avoid inconvenient short-or long-term complications such as inflammation, infection or allergy [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is easily made on the basis of clinical data including reference to an event which led to penetration by the foreign body and identification of a more or less extended area of inflammation. Removal of the foreign body is extremely important in order to avoid acute or chronic complications such as allergic reactions, inflammation or serious infections [1]. We report the US findings in a case where a wooden splinter had penetrated the subcutaneous soft tissues and caused formation of a phlegmon.…”
Section: Introductionmentioning
confidence: 94%
“…After our complete review of these articles and their reference sections and our limited reviews of other databases, we included 17 articles in this metaanalysis (Table 1). All 17 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] reported data for calculation of sensitivity; however, only 13 [23][24][25][26][27][28][29][30][31][32][33][34]36,37 reported data for calculation of specificity.…”
Section: Resultsmentioning
confidence: 99%